Post-tuberculosis lung disease patients benefit from vaccinations as other respiratory conditions - Giovanni Battista Migliori; Rosella Centis; Lia D’Ambrosio; Dina Visca; Onno W. Akkerman; Denise Rossato Silva; Daria Podlekareva; Yousra Kherabi (Monaldi Archives for Chest Disease)
Dear Editor, A joint statement of the Italian respiratory, infectious diseases and public health societies has been recently published on the best vaccination strategies in respiratory disease...